Plan de Marketing para el Grand Hotel Loja, ubicado en la Ciudad de Loja - Ramón Montaño, Elena Elizabeth (2016)
This research was developed with the aim of contributing to the management of the Grand Hotel Loja and with the purpose of proposing alternative solutions that contribute to the promotion and tourism development of the establishment. With the purpose of correcting failures presented in the company such as: the lack of a marketing plan for the proper operation of the hotel, lack of advertising by the different media and the lack of strategic alliances with companies in the tourism sector that Facilitate the promotion of its services, which is why it does not allow you to have competitive advantages that allow you to stay in the market and grow business. For the development of the project, it was necessary to use methods such as deductive, inductive and descriptive; As well as investigative techniques such as direct observation, the interview that was applied to the hotel manager, employee survey and a sample of 343 clients out of the 2,400 registered in the year 2015. The specific objectives proposed were achieved with the following results: the external analysis was carried out through the EFE Matrix, which generated a weighted factor of 2.84 indicating that the company is in an environment of opportunities, Support of the government to the sector through the generation of local and national tourist programs, as well as the labor legislation that implies better relations between the employees and the employer facilitating a better work environment. Regarding the analysis of the competitive sector, the PC matrix was elaborated through the results of the five PORTER forces, where it is recognized that the sector is highly competitive, and identifying two leaders, one being the Grand Hotel Loja with one Average position In the internal analysis, the EFI Matrix was used, with a weighted value of 2.99, indicating that the hotel is slightly stronger than weak, its main strengths being the strategic location when it is in the center of the city, besides having Various services and a fixed client portfolio. Finally, we proceed to make the cross-factors in the matrix of high impact SWOT where the strategic objectives for the marketing plan are established as follows: 1) Generate a more efficient and effective performance by sales personnel, which consists of 2 training workshops, with a cost of $ 2,000.00 per year. 2) Dissemination through an advertising campaign the services offered by the hotel to be recognized locally, nationally and internationally, which consists of a wedge and advertisement with a value of $ 1,015.00 per year. 3) To increase the positioning and the profitability of the hotel in the tourist market, for which a curriculum of the services and products offered was designed, as well as a presentation card of the Sales Manager, which will be delivered to companies of the medium seeking A strategic alliance that generates common benefits, with an estimated budget of $ 245.00. 4) Incursing in new market segments that are not covered by the hotel, for which it is proposed to develop a market research which has a cost of $ 3,000.00. Once detailed the activities to be carried out in each of the objectives, as well as the goals and tactics necessary for their fulfillment, a general budget of $ 6,260.00 is obtained, which will be fully financed by the shareholders' meeting of the Grand Hotel Loja, during the five years of project execution.